صعوبات تعليم اللغة العربية للناطقين بها والناطقين بغيرها - سليمان، يحي زكريا حسن; الزاكى، آدم محمد أحمد الحاج (جامعة السودان للعلوم والتكنولوجيا - عمادة البحث العلمي, 2020)
شرف الله تعالى اللغة العربية بأن جعلها لغة لكتابه العزيز، فتكفل بحفظها وصونها فأصبح العمل على تعليمها ونشرها من الأمور المقدسة، لأن في تعليمها نشر للقرأن الكريم وسنة نبينا محمد صلي الله عليه وسلم، وانبرى لهذه القضية الحادبون من أبناء الأمة الإسلامية على تعليمها ونشرها، لكن الناظر إلى مسألة تعليم اللغات في هذا العصر يجد أن الجهود المبذولة لتعليم ونشر العربية أقل بكثير مما يبذل تجاه اللغات الأخرى مما يشكل تحديا كبيرا أمام القائمين على هذا الأمر. هدفت الدراسة إلى: لفت النظر إلى الجهود التي كانت تبذلها الأمم السابقة اهتماما بلغاتها والأساليب والطريقة التي تتخذها تجاه التعليم والتعلم، التعرف على مفهوم طريقة التدريس وإجراءاتها، والتعرف على المعايير والأسس التي تفضل بها كل طريقة عن آخري، والتعرف على أشهر وأحدث طرائق تعليم اللغة العربية ونشأتها ومدخل كل طريقة. اتبعت الدراسة المنهج الوصفي الاستقرائي التحليلي. بعد الدراسة تم استخلاص النتائج التي توصلت إليها في الاتي: عدم ملائمة المقرر لأهداف تعليم اللغة العربية يؤدي إلى صعوبة في تعليم اللغة العربية، عدم ملائمة المنهج لبيئة وثقافة المجتمع والذي يؤدي إلى صعوبة في تعليم وتعلم اللغة العربية. يوجد صعوبات في تعليم وتعلم اللغة العربية متعلق بالتقويم. توصي الدراسة بالآتي: بذل المزيد من الجهود في تحديد أنسب الطرائق لتعليم اللغة العربية واللغات الأجنبية، إقامة معاهد لتدريب وتأهيل المعلمين الذين يتولون تدريس اللغات، بحيث تزيد من تحصيل المتعلمين وتساعد المعلم في تحقيق الأهداف.
Allah honored the Arabic language by making it the language of his holy book, so it's perfectly preserved and teaching and publishing it became a holy matter. The pilgrims of the Islamic nation have published and spread the Holy Qur'an and the Sunnah of our Prophet Muhammad, peace and blessings be upon him. But the one who looks at the issue of teaching languages in this era finds that the efforts made to teach and spread Arabic are much less than what is being done towards other languages, which poses a great challenge to those in charge of this matter. The study aimed to draw attention to the efforts made by the previous nations with interest in their languages and methods and the way they take towards teaching and learning, to identify the concept of the teaching method and its procedures, and to identify the criteria and foundations by which each method is preferred over the other, and to identify the most famous and recent methods of teaching the Arabic language and its emergence and entrance to each method. The study followed the descriptive and inductive analytical approach. After the study, the results were reached in the following: the lack of suitability of the curriculum for the aims of teaching the Arabic language leads to difficulty in teaching the Arabic language, the inadequacy of the curriculum for the environment and culture of society leads to difficulty in teaching and learning the Arabic language. There are difficulties in teaching and learning the Arabic language related to the calendar. The study recommends the following: More efforts should be made in determining the most appropriate methods for teaching Arabic and foreign languages, setting up institutes for training and qualifying teachers who teach languages, so as to increase the achievement of learners and help the teacher in achieving the goals.
Keywords: صعوبات التعلم -- الناطقين بغير العربية -- النحو العربي -- اللغة العربية